Efficient ion acceleration and dense electron–positron plasma creation in ultra-high intensity laser-solid interactions - D Del Sorbo; D R Blackman; R Capdessus; K Small; C Slade-Lowther; W Luo; M J Duff; A P L Robinson; P McKenna; Z-M Sheng; J Pasley; C P Ridgers (New Journal of Physics, 2018)
The radiation pressure of next generation ultra-high intensity (>10 ^23 W cm ^−2 ) lasers could efficiently accelerate ions to GeV energies. However, nonlinear quantum-electrodynamic effects play an important role in the interaction of these laser pulses with matter. Here we show that these effects may lead to the production of an extremely dense (∼10 ^24 cm ^−3 ) pair-plasma which absorbs the laser pulse consequently reducing the accelerated ion energy and laser to ion conversion efficiency by up to 30%–50% and 50%–65%, respectively. Thus we identify the regimes of laser-matter interaction, where either ions are efficiently accelerated to high energy or dense pair-plasmas are produced as a guide for future experiments.